An overall review on Obesity and its related disorders - SAILAJA, A.KRISHNA (Innovare Journal of Life Sciences, 2015)
Obesity can be defined as an excess proportion of total body fat. Obesity is increasing rapidly around the world. Nearly 20-25 % of the children are either overweight or obese. More than 80 % of the deaths in U.S are in patients with body mass index over 30. If the BMI is more than 40, life span is going to be reduced as much as 20 years for men and five years for women. Obesity develops number of chronic diseases like insulin resistance, Type 2 diabetes, hypertension, congestive heart failure. In this review the role of dietary modifications, genetic background and life style modifications in the prevalence of obesity was discussed. Its main reasons, complications and treatment of obesity were also explained in detail manner. Measurements to be taken to control the weight, importance of physical activity were also given significance in this article.